Identification of potential SARS-CoV-2 Mpro inhibitors integrating molecular docking and water thermodynamics. Issue 11 (28th June 2022) - Sobhia, M. Elizabeth; Ghosh, Ketan; Sivangula, Srikanth; Kumar, Siva; Singh, Harmanpreet
Abstract: The COVID-19 pandemic is an ongoing global health emergency caused by a newly discovered coronavirus SARS-CoV-2. The entire scientific community across the globe is working diligently to tackle this unprecedented challenge. In silico studies have played a crucial role in the current situation by expediting the process of identification of novel potential chemotypes targeting the viral receptors. In this study, we have made efforts to identify molecules that can potentially inhibit the SARS-CoV-2 main protease (M pro ) using the high-resolution crystal structure of SARS-CoV-2 M pro . The SARS-CoV-2 M pro has a large flexible binding pocket that can accommodate various chemically diverse ligands but a complete occupation of the binding cavity is necessary for efficient inhibition and stability. We augmented glide three-tier molecular docking protocol with water thermodynamics to screen molecules obtained from three different compound libraries. The diverse hits obtained through docking studies were scored against generated WaterMap to enrich the quality of results. Five molecules were selected from each compound library on the basis of scores and protein-ligand complementarity. Further MD simulations on the proposed molecules affirm the stability of these molecules in the complex. MM-GBSA results and intermolecular hydrogen bond analysis also confirm the thermodynamic stability of proposed molecules. This study also presumably steers the structure determination of many ligand-main protease complexes using x-ray diffraction methods. Communicated by Ramaswamy H. Sarma